Evaluation of shear bond strength of orthodontic brackets bonded with Er-YAG laser etching - S Hamid Raji; Reza Birang; Fateme Majdzade; Reza Ghorbanipour (Dental Research Journal, 2012)
Background: Based on contradictory findings concerning the use of lasers for enamel etching, the purpose of this study was to investigate the shear bond strength of teeth prepared for bonding with Er-YAG laser etching and compare them with phosphoric acid etching. Materials and Methods: In this in vitro study forty - eight premolars, extracted for orthodontic purposes were randomly divided in to three groups. Thirty-two teeth were exposed to laser energy for 25 s: 16 teeth at 100 mj setting and 16 teeth at 150 mj setting. Sixteen teeth were etched with 37% phosphoric acid. The shear bond strength of bonded brackets with the Transbond XT adhesive system was measured with the Zwick testing machine. Descriptive statistics, Kolmogorov-Smirnov test, of homogeneity of variances, one- way analysis of variances and Tukey′s test and Kruskal Wallis were used to analyze the data. Results: The mean shear bond strength of the teeth lased with 150 mj was 12.26 ± 4.76 MPa, which was not significantly different from the group with acid etching (15.26 ± 4.16 MPa). Irradiation with 100 mj resulted in mean bond strengths of 9.05 ± 3.16 MPa, which was significantly different from that of acid etching (P < 0.001). Conclusions: laser etching at 150 and 100 mj was adequate for bond strength but the failure pattern of brackets bonded with laser etching is dominantly at adhesive - enamel interface and is not safe for enamel during debonding.